Pelatihan Pengaman Instalasi Listrik Menggunakan RED (Residual Current Device) di Br. Sambian Undagi, Ds. Timpag, Kec. Kerambitan-Tabanan - Partha, C. G. I.; Janardana, I. G. N.; Weking, A. I. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi, 2016)
For people in their recent life, electricity is extremely vital. It becomes a primer necessity due to the facts that almost all of our supporting life equipments need electricity to be operated. In addition to its huge benefit, electricity also contains dangers that could cause decease for its user. However, electricity danger could be removed by following every electricity installation requirements. Electricity-sting danger could be surmounted by using RCD (Residual Current Device). Usage of RCD on the 2011 common requirement for electricity installation (PUIL), and the 2014 amandement, hints that to secure environment, in this case human being, it is a compulsory for using RCD. At the Sambian Undagi, Timpag village, Kerambitan districts, Tabanan regency, most of the electricity installations do not match the standard, and no one uses electrical protection for a direct and indirect touch. By implementing RCD, the danger for being stung both direct or indirect could be reduced, and so, there are no longer fatal accidents caused by electricity.
Keywords: electricity, installation, protections, PUIL, RCD (residual current device)